Systems of Systems with Security - Lauritsen, Rasmus Winther (Technical Report Electronics and Computer Engineering, 2013)
In this report we present two case studies with Systems of Systems modelling. One model illustrates how Cryptographic parameter consistency can be checked using VDMPP for a System of Systems uses encryption to enforce Digital Right Management. The other model shows how a new formalism (CML) tailored specifically to Systems of Systems can express Multi-Party Computation protocol. The idea of using Canetti simulation proofs from Multi-Party computation as a model for refinement of models in CML is presented. Our goal is modest. We do not aim at proving security through refinement but to assists modellers/developers in maintaining security properties during refinement of a concept to designs.